Vegetables contamination by heavy metals and associated health risk to the population in Koka area of central Ethiopia. - Leta Danno Bayissa; Hailu Reta Gebeyehu (PLoS ONE)
Contaminated soil and vegetables have continued to instigate threat to human health globally and specially in developing countries. This study was aimed to determine concentrations of certain heavy metals in soil and vegetables (cabbage and tomato) from Koka area of central Ethiopia using Inductively Coupled Plasma Optical Emission Spectrophotometer (ICP-OES). The amounts of As, Pb, Cd, Zn, Cu, Hg and Co detected in soil samples were found to surpass the reference values for agricultural soil. Similarly, the concentrations of As, Pb, Cd, Cr and Hg obtained in both tomato and cabbage samples have exceeded the recommended values with the mean levels generally ranging from 0.93-6.76, 1.80-7.26, 0.33-1.03, 0.86-5.16 and 3.23-4.36 mg/kg dry weight, respectively. The result obtained have signified that leafy vegetable has hoarded heavy metals more than non-leafy vegetable. The total hazard quote for As and Hg from tomato ingestion and for As, Hg and Co from cabbage ingestion were greater than unity, signifying potential health hazard to the public. The health index (HI) owing to tomato and cabbage ingesting were 5.44 and 14.21, respectively, signifying likely adversative health implication to the population from the ingestion of the vegetables. The Total Cancer Risk (TCR) analysis have uncovered the possible cancer hazard persuaded by Cd, Hg, As and Ni from the ingestion of both vegetables. From the outcomes this study, it can be concluded that the soil and vegetables from Koka areas are possibly contaminated with toxic metals and hence demand strict monitoring to safeguard the public around the study area and beyond.